Internationalization in architecture higher education: A strategy of studio immersion from the students’ Perspective - Damayanti, Rully; Wijaya, Elvina; Wayne, Bram Michael; Kasemsook, Apriradee; Chiu , Kuowei Eleazar-Godfrey (Journal of International Students, 2024)
In this paper, we investigate the perspective of students who have performed studio immersion, which consists of three Asian universities in batches 2022 and 2023, with a total of 147 students from Indonesia, Thailand, and Taiwan. We used mixed methods research to identify real obstacles and challenges and to determine to what extent this study benefits students. The results show that the students experience a progressive understanding of personal development, a broader meaning of architecture beyond technical and aesthetic systems but social and cultural, and an understanding of architecture as a multifaceted profession. The students reported their dissatisfaction with the pursuit of the university’s reputation, studio dynamics, and uncertainty in the assignment’s limitations. English interaction among students is not affected by their early exposure to English for their generation. This type of studio immersion could create a new studio culture that is unique to a global learning experience.